2013
DOI: 10.1149/2.001305eel
|View full text |Cite
|
Sign up to set email alerts
|

Probing Electrode Losses in All-Vanadium Redox Flow Batteries with Impedance Spectroscopy

Abstract: We report on single-electrode electrochemical impedance spectroscopy studies of an all-vanadium redox battery using a dynamic hydrogen reference electrode. The negative electrode, comprising the V 2+ /V 3+ couple, contributes approximately 80% of the total cell overpotential during discharge. The impedance spectra measured at the negative electrode exhibit high-frequency, semicircular arcs which correspond to the double layer capacitance in parallel with a faradaic resistance. The faradaic resistance decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
117
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 7 publications
5
117
0
Order By: Relevance
“…Most studies in the past, however, report overall battery parameters (cell resistance or efficiency) and hence conclude with rather general statements. More detailed investigations using reference electrodes or non‐symmetric felt combinations at the positive and negative electrodes have shown that the negative electrode is more problematic with respect to the kinetic overpotential. In fact, recent systematic studies of the electrochemical pretreatment of various carbons (glassy carbon, carbon fibers, graphite) have even revealed opposing effects for both redox couples when subjected to anodic or cathodic pre‐treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies in the past, however, report overall battery parameters (cell resistance or efficiency) and hence conclude with rather general statements. More detailed investigations using reference electrodes or non‐symmetric felt combinations at the positive and negative electrodes have shown that the negative electrode is more problematic with respect to the kinetic overpotential. In fact, recent systematic studies of the electrochemical pretreatment of various carbons (glassy carbon, carbon fibers, graphite) have even revealed opposing effects for both redox couples when subjected to anodic or cathodic pre‐treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon materials, and carbon felts in particular, are conventionally used in VRFB electrodes. The slow rates of these reactions are a serious problem in VRFB technology, which must be solved to improve the efficiency of VRFBs . We found that a 3D RGO network was successfully formed in a loosely entangled carbon‐fiber matrix and that the activity for the vanadium redox reactions was correlated to the network structure.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Two promising technologies are the all-vanadium RFB (VRB) and the hydrogen/bromine RFB, where good performances have been demonstrated recently. [6][7][8][9][10][11][12][13][14] Protons in a cation-exchange membrane (CEM) typically carry charge between the two electrodes in these two RFBs. In both systems, movement of reactant or product species from one electrode to the other through the membrane results in inefficiency and reversible capacity loss.…”
mentioning
confidence: 99%